Policy development Urban Street Vendors in Sidoarjo Post-Reformation : Perkembangan Kebijakan Tata Kelola Pedagang Kaki Lima di Sidoarjo Pasca Reformasi - Moch. Ichyak Ulumuddin; Rifqi Ridlo Phahlevy (Academia Open, 2020)
The Government of Sidoarjo Regency in establishing policies regarding the arrangement of Street Vendors (PKL) aims to create a clean, orderly and beautiful Sidoarjo Regency and continue to empower existing street vendors. The spatial planning policy implemented by the Sidoarjo Regency Government is aimed at maintaining and structuring a more orderly and orderly spatial location without ignoring the existence of street vendors who aim to improve the economy of their families. This study aims to find out how the Sidoarjo Regency Government's policy in structuring street vendors (PKL) based on traders, order and beauty, this study uses descriptive research methods using a qualitative approach. The results of the study indicate that the PKL structuring policy is closely related to the plan to create a clean, orderly, safe, and comfortable city spatial plan. So that in its formulation, an alternative policy that is aware of the environment is needed. The government of Sidoarjo Regency so far has made significant efforts in structuring street vendors in the Sidoarjo Regency area and to overcome and anticipate the impacts. The implementation of the street vendor management policy (PKL) based on the Sidoarjo Regional Regulation No. 3 of 2016 concerning the arrangement and empowerment of street vendors has been running but has not been effective, such as the resistance that occurs when the implementation of the PKL arrangement takes place, it should be able to be overcome if the Sidoarjo Regency Government is responsive enough to various demands from street vendors.